Provenance trial of acacia auriculiformis in Peninsular Malaysia: 12 - month performance - Ab Shukor, Nor Aini; Awang, Kamis; Mohd Rashid, Mansor; Senin, Abd Latib (Forest Research Institute Malaysia, 1994)

(untitled)
A trial of 28 provenances of Acacia auriculiformis was assessed for sunival and growth at age 12 months. Of these provenances, 7 were from Queensland and 15 from Northern Territory, Australia, and 6 from Papua New Guinea. All provenances survived very well ( gt 92%), but they differed very significantly (p lt 0.001) in their growth performance. A selection of provenances from Northern Territory and Queensland were among the top performers, with East Alligator River (16152) being the best. The results indicate the presence of genetic diversity in this species and support the need for genetic improvement.